Employee Job Security, Emotional Stability and Adaptability in Predicting Employee Retention among Gen Z Employees - Rifa Amalia; Sugeng .; Salsa Tri Wulandari Deputri; Dedi Muhammad Siddiq; Bachrudin Syaroni; Tismazammi Mustafa (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study aims to discuss job security, emotional stability and adaptability in predicting employee retention of Gen Z employees in Indonesia.